A luminous polypropylene composite material, a preparation method and application thereof

CN122941094APending Publication Date: 2026-10-20SOUTH CHINA NORMAL UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611125273.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

目前的夜光粉主要存在以下难题:一是稀土夜光粉本身遇水会水解失效;二是在塑料加工中,夜光粉的加入会影响其力学性能,且夜光粉的改性会导致其余辉性能受到限制

Benefits of technology

[0022]本发明的第三方面提供了一种如本发明的第一方面所述的夜光聚丙烯复合材料在夜光设备中的应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a luminescent polypropylene composite material, its preparation method, and its applications. The luminescent polypropylene composite material comprises the following components in parts by weight: 150-250 parts polypropylene, 1-12 parts modified phosphor, 8-12 parts modified talc, 8-12 parts maleic anhydride, and 2-6 parts foaming agent. The modified phosphor includes aminosilane coupling agent-modified phosphor, melamine-formaldehyde resin-coated phosphor, or a combination thereof. The modified talc includes aminosilane coupling agent-modified talc. This invention uses specific modified phosphor, modified talc, maleic anhydride, and foaming agent to compound with polypropylene, providing a long afterglow time while exhibiting good bending and tensile properties, meeting the requirements of most rigid structural components. It has wide applications in luminescent devices where afterglow is the primary function and long-term performance is required, such as luminescent emergency indicator devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials technology, and particularly relates to a luminescent polypropylene composite material, its preparation method, and its application. Background Technology

[0002] The functional integration of polymer materials is an important development direction in the field of materials science. Luminescent properties, due to their unique advantages in passive lighting, safety warnings, and visual traceability, have become a hot topic for adding value to polymer materials. Polypropylene (PP) is polymerized from propylene monomers through an addition polymerization reaction and possesses a series of excellent comprehensive properties. By adding luminescent powder to PP, the material can be endowed with luminescent properties. However, without special treatment, the exposed luminescent molecules in the luminescent powder are very fragile and easily degraded by oxygen, moisture, high temperature, and chemicals. Therefore, modification technology is the core to ensure the stability of luminescent powder performance. Current luminescent powders mainly face the following challenges: firstly, rare earth luminescent powders themselves hydrolyze and degrade upon contact with water; secondly, in plastic processing, the addition of luminescent powder affects its mechanical properties, and the modification of luminescent powder limits its afterglow performance. Summary of the Invention

[0003] In order to solve at least one of the problems existing in the prior art, one of the objectives of the present invention is to provide a luminescent polypropylene composite material that can provide a long afterglow time while having good bending and tensile properties, meeting the usage requirements of most rigid structural components, and suitable for application scenarios where afterglow is the main function and long-term service performance is required.

[0004] The second objective of this invention is to provide a method for preparing the above-mentioned luminescent polypropylene composite material.

[0005] The third objective of this invention is to provide an application of the above-mentioned luminescent polypropylene composite material.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A first aspect of the present invention provides a luminescent polypropylene composite material comprising the following components in parts by weight: 150-250 parts polypropylene, 1-12 parts modified phosphor, 8-12 parts modified talc, 8-12 parts maleic anhydride, and 2-6 parts foaming agent; wherein the modified phosphor comprises aminosilane coupling agent modified phosphor, melamine-formaldehyde resin coated phosphor, or a combination thereof; and the modified talc comprises aminosilane coupling agent modified talc.

[0007] In some embodiments of the present invention, the aminosilane coupling agent is selected from γ-aminopropyltriethoxysilane (KH550).

[0008] In this invention, the aminosilane coupling agent modification introduces a large number of chemical defects on the phosphor surface. These sites can act as effective trap energy levels to capture photogenerated carriers generated during excitation. Furthermore, the charge transfer complex formed by the amino functional groups on the phosphor surface also increases the trap density, which is beneficial for improving afterglow performance. In addition, the interface between the modified talc and phosphor particles generates abundant interface defect states due to lattice mismatch and surface energy differences, which also participate in carrier capture. The addition of maleic anhydride and a foaming agent further modifies the interface state and local stress field, optimizing the depth distribution of the traps. This invention selects KH550 as a modifier for both the phosphor and talc, which reacts with maleic anhydride to achieve better interface enhancement and generate a large number of chemical defects, effectively improving afterglow performance while ensuring good long-term mechanical properties.

[0009] In some embodiments of the present invention, the aminosilane coupling agent content in the aminosilane coupling agent modified phosphor is 1-5%; for example, it can be any value of 1%, 2%, 3%, 4%, 5% or any range between two; in some specific embodiments of the present invention, the aminosilane coupling agent content in the aminosilane coupling agent modified phosphor is 2-4%.

[0010] In some embodiments of the present invention, the aminosilane coupling agent content in the aminosilane coupling agent modified talc powder is 1-5%; for example, it can be any value of 1%, 2%, 3%, 4%, 5% or any range between two; in some specific embodiments of the present invention, the aminosilane coupling agent content in the aminosilane coupling agent modified talc powder is 2-4%.

[0011] In some embodiments of the present invention, the melamine-formaldehyde (MF) resin-coated phosphor is prepared by a method comprising the following steps: mixing melamine, formaldehyde and water to obtain a melamine-formaldehyde prepolymer solution; mixing the melamine-formaldehyde prepolymer solution, phosphor and an acidic compound, and performing a polymerization reaction to obtain the melamine-formaldehyde resin-coated phosphor.

[0012] In some embodiments of the present invention, the modified phosphor is selected from aminosilane coupling agent modified phosphor; in some specific embodiments of the present invention, the modified phosphor is selected from γ-aminopropyltriethoxysilane (KH550) modified phosphor.

[0013] In some embodiments of the present invention, the mass of the modified phosphor is 0.05 to 6% of the mass of the polypropylene; for example, it can be any value or a range between any two of 0.05, 1%, 2%, 3%, 4%, 5%, or 6%; in some specific embodiments of the present invention, the mass of the modified phosphor is 4 to 6% of the mass of the polypropylene.

[0014] In some embodiments of the present invention, the phosphor raw materials used in the modified phosphor include at least one of chlorosilicate phosphor, oxynitride phosphor, rare earth aluminate phosphor, or perovskite phosphor.

[0015] In some embodiments of the present invention, the mass of the modified talc is 3 to 7% of the mass of the polypropylene; for example, it can be any value of 3%, 4%, 5%, 6% or 7% or a range between any two; in some specific embodiments of the present invention, the mass of the modified talc is 4 to 6% of the mass of the polypropylene.

[0016] In some embodiments of the present invention, the foaming agent includes at least one of azobisisobutyronitrile, azodicarbonamide, ammonium bicarbonate, or sodium bicarbonate.

[0017] In some embodiments of the present invention, the components of the luminescent polypropylene composite material also include white oil.

[0018] In some embodiments of the present invention, the mass of the white oil is 0.05 to 2% of the mass of the polypropylene.

[0019] A second aspect of the present invention provides a method for preparing a luminescent polypropylene composite material as described in the first aspect of the present invention, comprising the following steps: mixing the components and extruding and granulating them to obtain the luminescent polypropylene composite material.

[0020] In some embodiments of the present invention, the extrusion granulation temperature is 180~220°C; in some specific embodiments of the present invention, the extrusion granulation temperature is 190~210°C.

[0021] In some embodiments of the present invention, the screw speed of the extrusion granulation is 20~40 r / min; in some specific embodiments of the present invention, the screw speed of the extrusion granulation is 25~35 r / min.

[0022] A third aspect of the present invention provides the application of the luminescent polypropylene composite material as described in the first aspect of the present invention in luminescent devices.

[0023] In some embodiments of the present invention, the luminous device includes at least one of a luminous emergency indicator device, a luminous sign device, or a luminous lighting device.

[0024] The beneficial effects of this invention are: This invention uses specific modified phosphors, modified talc, maleic anhydride and foaming agents to compound with polypropylene, which can provide a long afterglow time while having good bending and tensile properties, meeting the usage requirements of most rigid structural components. It has wide applications in applications where afterglow is the main function and long-term use performance is required, such as luminous emergency indicator devices and other luminous devices. Attached Figure Description

[0025] Figure 1 The steady-state PL spectra of the PP samples obtained in each embodiment and comparative example are shown.

[0026] Figure 2 The DL-delayed spectra of the PP samples obtained in each embodiment and comparative example are shown.

[0027] Figure 3 These are afterglow images of the PP samples obtained in each embodiment and comparative example. Detailed Implementation

[0028] The following specific embodiments further illustrate the content of the present invention in detail. It should also be understood that the following embodiments are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Non-essential improvements and adjustments made by those skilled in the art based on the principles described herein are all within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make selections within a suitable range based on the description herein, and are not intended to be limited to the specific data in the examples below. Unless otherwise specified, the raw materials, reagents, or apparatus used in the following embodiments and comparative examples can be obtained from conventional commercial sources or by existing known methods.

[0029] It should be noted that the phosphor raw materials used in the embodiments of the present invention were purchased from Shanghai Chenlai Chemical and Shanghai Zuoyue New Materials. Specifically, the phosphor raw materials are rare earth aluminate phosphors; the foaming agent is sodium bicarbonate.

[0030] Preparation Example 1 A modified phosphor, surface-modified using silane coupling agent KH550, is prepared as follows: Take 0.6g of KH550 (accounting for 3wt% of the final product) in a beaker, add 10g of anhydrous ethanol, shake for 5 minutes, and then dropwise add it to 20g of phosphor raw material. Stir evenly with a high-speed stirrer (about 30s) to obtain modified phosphor.

[0031] Preparation Example 2 A modified talc powder, surface modified using silane coupling agent KH550, is prepared as follows: Take 0.6g of KH550 (accounting for 3wt% of the final product) in a beaker, add 10g of anhydrous ethanol, shake for 5 minutes, and then add it dropwise to 20g of talc powder raw material. Stir evenly with a high-speed mixer (about 30s) to obtain modified talc powder.

[0032] Preparation Example 3 An MF phosphor, surface-coated with MF resin, is prepared by the following method: Take 5.67g of formaldehyde aqueous solution (formaldehyde content 37wt%) in a round-bottom flask, add melamine to adjust the pH to 8-9, weigh 4.32g of melamine and add it to the round-bottom flask, shake well, heat in a water bath at 90℃ and stir until the solution becomes transparent and clear to obtain MF prepolymer solution. Take 9.4g of MF prepolymer solution in another round-bottom flask, add 12g of phosphor raw material and acetic acid solution, heat and stir at 80℃ for 1 hour, centrifuge and dry for 48 hours to obtain MF phosphor.

[0033] Examples 1-4 and Comparative Examples 1-6 Examples 1-4 and Comparative Examples 1-6 provide a series of luminescent PP composite materials, the preparation methods of which are as follows: Weigh 200g of PP, mix the raw materials according to the formula shown in Table 1, put the mixed raw materials into a twin-screw extruder, extrude and granulate at 30rpm and 200℃, and injection mold into standard test strips to obtain various luminous PP composite materials.

[0034] In Table 1, the percentage of each raw material refers to its mass percentage in PP. Modified phosphor, modified talc, and MF phosphor were prepared from Preparation Examples 1 to 3, respectively. Pure phosphor refers to unmodified phosphor raw materials.

[0035] Table 1. Raw material formulations in each embodiment and comparative example.

[0036] Performance testing The PP materials prepared in each embodiment and comparative example were used as test specimens and the following tests were conducted.

[0037] (1) Tensile test Tensile properties were tested according to GB / T 1040-2006 "Determination of Tensile Properties of Plastics". The specimens were stretched at a rate of 100 mm / min until fracture. The tensile strength and elongation at break of the test specimens were measured. Each test was repeated 6 times, and the arithmetic mean was taken.

[0038] (2) Bending test The bending performance was tested according to GB / T 9341-2008 "Determination of Flexural Properties of Plastics". The span was kept at 64 mm, and the bending was performed at a rate of 10 mm / min until the span was 20 mm. The bending strength and bending modulus were then tested. Each test was repeated 6 times, and the arithmetic mean was taken.

[0039] (3) Impact test Impact strength tests were conducted according to GB / T 1843-2008 "Determination of Impact Strength of Plastic Cantilever Beams". Each test was repeated 6 times, and the arithmetic mean was taken.

[0040] (4) Quality testing Weigh the different PP composite materials six times and take the arithmetic mean.

[0041] (5) Optical performance testing Different PP composite materials were placed in an analytical cell and their fluorescence / phosphorescence intensity was analyzed by scanning fluorescence spectra between 400 and 4000 nm.

[0042] The test results of the mechanical properties are shown in Table 2.

[0043] Table 2. Mechanical property test results of each embodiment and comparative example.

[0044] As shown in Table 2, the luminescent PP composite materials prepared in Examples 1-4 possess excellent mechanical properties, with tensile strength ≥39.7 MPa, elongation at break ≥21.7%, flexural strength ≥38.9 MPa, flexural modulus ≥1235.1 MPa, and cantilever beam notched impact strength ≥8.4 KJ / m. 2 In particular, the nominal fracture resistance of Examples 2-4 can be as high as 42.3%, and can reach as high as 128.7%. Although Comparative Examples 1-6 have certain tensile strength and strain properties, their bending strength, bending modulus and cantilever beam notched impact strength are not as good as those of Examples 1-4.

[0045] A comparison of Examples 1-4 and Comparative Examples 1-4 shows that the surface treatment method of the phosphor determines the interfacial bonding strength, thus dominating the failure mode of the composite material. Example 1 uses MF-coated phosphor, which provides the most robust physical protection, particularly achieving excellent flexural modulus. While the material's strain performance is slightly reduced, its overall mechanical properties are excellent. Examples 2-4 use KH550-modified phosphor, which has little effect on the tensile strength of the samples. Adding 1% to 5% of modified phosphor does not significantly change the tensile strength; however, both flexural strength and flexural modulus increase with increasing modified phosphor content. At 5% addition, both flexural strength and flexural modulus are higher, and the samples exhibit good plastic deformation capacity. Comparative Examples 1-4 use unmodified pure phosphor, which significantly affects the tensile strength of the samples. Increasing the pure phosphor content from 1% to 5% results in a noticeable decrease in tensile strength; while flexural strength decreases with increasing pure phosphor content, the flexural modulus slightly increases, and the material exhibits typical ductile fracture characteristics upon fracture.

[0046] The root cause of the above differences lies in the difference between the interfacial bonding strength and the deformation ability of the particles themselves. Examples 1-2 and Comparative Example 1, which only changed the phosphor treatment method, exhibited completely different mechanical characteristics.

[0047] In sample a of Example 1, MF resin forms a highly cross-linked thermosetting resin rigid shell on the phosphor surface, exhibiting the highest flexural modulus among all samples. This is attributed to the combined contribution of this rigid shell and talc. MF resin coating of the phosphor provides a dense physical barrier, effectively isolating moisture and oxygen, playing a crucial role in extreme environment protection. For phosphor systems extremely sensitive to water and oxygen (such as certain sulfide-based phosphors), it can effectively extend their luminescence lifetime. Furthermore, MF coating can prevent thermal oxidative degradation of the phosphor during high-temperature processing at 200°C, improving process stability.

[0048] In sample b of Example 2, one end of the silane coupling agent KH550 hydrolyzes and reacts with the hydroxyl groups on the surface of the phosphor, while the amino functional group at the other end can chemically react with maleic anhydride or polypropylene grafts to form a strong chemical bond or hydrogen bond network. This strong interfacial bonding results in better dispersion stability and anti-aging ability, significantly improving interfacial durability. After KH550 modification, the phosphor is anchored to the polypropylene matrix or maleic anhydride through chemical bonds, effectively resisting moisture erosion and interfacial fatigue under long-term loads. For products requiring long-term outdoor use or subjected to dynamic stress (such as automotive interior parts, outdoor signs, etc.), this modification brings significant reliability improvements. Furthermore, KH550 modification also improves the uniformity of phosphor dispersion in the matrix, preventing particle marks on the surface of injection-molded parts.

[0049] In sample e of Comparative Example 1, the unmodified phosphor surface is hydrophilic, resulting in poor compatibility with the hydrophobic polypropylene matrix and maleic anhydride. This leads to easy aggregation of the unmodified phosphor and easy interface deterioration under humid and hot environments, causing mechanical and luminescent properties to decay over time. Consequently, it results in poor long-term reliability, environmental adaptability, and processing stability. Although sample e exhibits good short-term mechanical properties, its poor long-term mechanical properties limit its suitability for disposable products that are cost-sensitive, used in mild environments, and do not require high long-term reliability.

[0050] Rigid filler talc has a significant restraining effect on the plastic flow of the matrix, and adding talc can effectively improve the stiffness and flexural modulus of the material. Modified talc, as a sheet-like rigid filler, can significantly improve the flexural modulus and flexural strength of composite materials. Foaming agents can reduce the density of materials to achieve lightweighting and slightly increase the flexural modulus. Maleic anhydride can form chemical bonds to strengthen the interface in the KH550 modified system, but only plays a physical compatibilizing role in the unmodified system, without changing the weak interface nature. The role of maleic anhydride is to react with the amino groups on the surface of KH550 modified phosphor to form chemical bonds, thereby enhancing the interfacial bonding; for unmodified phosphor, maleic anhydride only plays a physical compatibilizing role and cannot change the weak interface state.

[0051] Examples 1-4 of this application demonstrate that through the synergistic effect of modified phosphor, modified talc, maleic anhydride, and foaming agent, a composite PP material with both high rigidity and good long-term reliability can be obtained. Furthermore, the KH550 modified phosphor and the MF-coated phosphor have different performance focuses. The KH550 modified phosphor can achieve better ductility, while the MF-coated phosphor is beneficial for achieving better weather resistance.

[0052] In addition, optical performance tests were conducted. Steady-state light intensity and delayed-motion spectroscopy tests were performed on each group of polypropylene-based phosphor composite materials prepared in the examples and comparative examples. Steady-state light intensity reflects the instantaneous luminescence efficiency of the material under continuous excitation conditions, mainly depending on the intrinsic quantum efficiency of the phosphor, the excitation light absorption efficiency, and the scattering and absorption losses within the material. Delayed-motion spectroscopy, measured at a specific delay time point after excitation stops, mainly reflects the ability of the trap energy levels in the phosphor to capture and release charge carriers, and is a key indicator for evaluating long-afterglow performance. The test results of optical performance are shown in […]. Figures 1-3 .

[0053] Figure 1 The PL steady-state spectra of the PP samples obtained in each embodiment and comparative example are shown, wherein the excitation wavelength is 330 nm. Figure 2 The DL-delayed spectra of the PP samples obtained in each embodiment and comparative example are shown, wherein the excitation wavelength is 330 nm and the delay time is 0.1 s. Figure 3These are afterglow images of the PP samples obtained in each embodiment and comparative example. Among them, UV OFF 0min, UV OFF 20min, UV OFF 40min, UV OFF 60min, UV OFF 80min, UV OFF 100min, and UV OFF 120min refer to the afterglow images at the instant the lights were turned off and 20min, 40min, 60min, 80min, 100min, and 120min after the lights were turned off, respectively.

[0054] according to Figure 1 As can be seen, the steady-state fluorescence intensity of each sample, from highest to lowest, is: h > g > f > d > c > a > b > e. According to... Figure 2 As can be seen, the afterglow intensity (delay 0.1s) of each sample, from high to low, is: d > c > g > b > f > a > e > h. The steady-state spectroscopy and DL delayed spectroscopy results show significantly different ranking patterns, indicating that steady-state luminescence and afterglow luminescence are dominated by different physical mechanisms, and that each formulation exhibits different performance in these two dimensions. Samples a~d prepared in Examples 1-4 have good afterglow intensity and also have relatively good fluorescence intensity, achieving a balance between afterglow intensity and fluorescence intensity.

[0055] Specifically, regarding fluorescence intensity, Comparative Example 1 uses a system with low content of unmodified phosphor and talc, namely sample e. In the presence of talc, the unmodified phosphor has poor dispersibility and is prone to forming agglomerates, which leads to concentration quenching and self-absorption. At the same time, the scattering effect of talc is more prominent in the low content of phosphor, resulting in a further reduction in fluorescence intensity.

[0056] Regarding the afterglow intensity, the trap source of sample e is only the weak interface between unmodified phosphor and talc, which has low density and low content, resulting in a shorter afterglow.

[0057] Regarding fluorescence intensity, the systems in Comparative Examples 2-4, which used unmodified phosphors and contained no additives or talc (i.e., samples h, g, and f), exhibited the highest steady-state fluorescence intensity, with the intensity increasing with increasing phosphor content. This is because the phosphors in these samples had never been exposed to aqueous treatment and had not undergone any surface coating or modification reactions, thus preserving their original crystal structure and surface chemical state, resulting in the highest quantum efficiency. Simultaneously, the absence of talc avoided the strong scattering and absorption of excitation and emission light by the white flake filler, allowing light to be emitted more effectively from the sample surface.

[0058] However, regarding afterglow intensity, sample h, which exhibited the highest fluorescence intensity, displayed the lowest afterglow intensity. This is because the unmodified phosphor surface has very few intrinsic defects and lacks water contact and chemical modification, resulting in a very low trap density. Furthermore, the absence of talc means no additional interface defect contribution. Therefore, although sample h had the highest brightness under steady-state excitation, almost no charge carriers were trapped and slowly released after excitation ceased, resulting in extremely weak afterglow. Similarly, samples g and f, which also used unmodified phosphors, also exhibited limited afterglow performance due to the limited intrinsic defects inherent in the unmodified phosphors themselves.

[0059] Regarding fluorescence intensity, the systems in Examples 2-4, which used KH550-modified phosphor and contained talc (i.e., samples d, c, and b), exhibited suboptimal steady-state fluorescence intensity. Specifically, samples d and c, with higher phosphor contents, showed higher steady-state light intensity than sample b, which had lower phosphor contents. This is because the phosphor undergoes brief contact with the alcohol-water solution during KH550 modification, causing some surface hydrolysis and defect introduction, resulting in a slight decrease in intrinsic luminescence efficiency. Simultaneously, the presence of talc causes light scattering losses, further reducing the emitted light intensity. The high phosphor content partially compensated for these losses, allowing samples d and c to maintain a moderately high steady-state light intensity.

[0060] Regarding the afterglow intensity, the outstanding performance of samples b, c, and d in the delayed spectra of Examples 2-4 stems from the synergistic effect of multiple factors. First, the KH550 modification introduces a large number of chemical defects on the phosphor surface, which can serve as effective trap energy levels to capture photogenerated carriers generated during excitation; the charge transfer complex formed between the amino functional groups of the silane coupling agent and the phosphor surface also increases the trap density. Second, the interface between the modified talc and phosphor particles generates abundant interface defect states due to lattice mismatch and surface energy differences, which also participate in carrier capture; and the addition of maleic anhydride and foaming agent further modifies the interface state and local stress field, optimizing the depth distribution of the traps. The higher phosphor content of samples d and c also provides more total trap sites; the higher the phosphor content, the more total trap sites are provided. Sample b has a lower phosphor content, thus its afterglow is at a moderate level.

[0061] It is worth noting that the mild water damage experienced by the phosphor during the KH550 modification process has a double-edged sword effect. Although the steady-state fluorescence intensity is slightly lower than that of the unmodified phosphor, the water-induced surface hydroxyl groups and local lattice disorder are ideal trap sources, which have a significant effect on enhancing the afterglow.

[0062] Regarding fluorescence intensity, the steady-state light intensity of sample a, which used MF-coated phosphor in Example 1, was lower than that of the KH550 modified system. This is mainly because the MF coating process involves a long-term hydrothermal treatment at 60 degrees Celsius for one hour under acidic conditions. The phosphor used is extremely sensitive to water, and severe surface hydrolysis, lattice corrosion, or destruction of luminescent centers occurred during this process, leading to irreversible degradation of optical performance. Although the MF coating layer itself is transparent, the intrinsic luminescence ability of the phosphor is significantly reduced.

[0063] Regarding the afterglow intensity, sample a had only a moderate afterglow level because the coating layer may have blocked the defects on the phosphor surface, and the surface was covered by resin after severe water damage.

[0064] In summary, comparing the above two sets of test results for fluorescence intensity and afterglow intensity clearly shows that in the material system of this invention, it is difficult to simultaneously achieve high steady-state light intensity and high delayed light intensity; there is a clear trade-off between the two. The unmodified phosphor and talc-free samples provided in Comparative Examples 2-4, especially sample h, excel in steady-state light intensity and are suitable for applications requiring high instantaneous brightness without afterglow, such as general lighting, display backlighting, and decorative illumination. These samples have high luminous efficiency, but while visible, they do not retain light effectively, exhibiting weak afterglow.

[0065] The KH550-modified phosphors and high-talc-content samples provided in Examples 2-4, especially sample d, excel in delayed light intensity and are suitable for applications requiring long afterglow characteristics, such as luminous safety signs, emergency evacuation indicators, and low-light illumination in dark environments. They can continue to emit light for a relatively long time after excitation stops, but their relative brightness during excitation is moderate. The slight damage caused by short-term, mild water contact in the KH550 modification is an acceptable loss in steady-state light, but it is converted into gain in delayed light. This indicates that mild, controllable surface hydrolysis and chemical modification can be an effective means of enhancing afterglow.

[0066] The KH550 modified phosphor, with a high content of talc, as shown in sample d, achieved the highest delayed light intensity, suitable for long-afterglow emergency indication. Talc exhibits a dual effect in optical properties: it is a harmful scattering center in steady-state light, but a beneficial trapping synergist in delayed light. The short-term alcohol-water treatment used in KH550 modification can be an effective method for controlling trap density and enhancing afterglow, but conditions must be strictly controlled to minimize excessive sacrifice of steady-state light efficiency.

[0067] In summary, regarding optical performance, the formulations exhibiting the highest afterglow intensity in delayed-motion spectroscopy are those in Examples 2-4, which utilize KH550 surface modification, high phosphor content, and modified talc. The afterglow is strongest at 5% phosphor content, followed by 3%. This combination significantly enhances carrier trapping and slow release capabilities through the synergistic effects of surface defects introduced by KH550, trap levels contributed by the talc interface, and mild water damage. The MF-coated phosphor system in Example 1 also achieves a certain level of afterglow and fluorescence intensity, making it suitable for afterglow applications. While the systems in Comparative Examples 1-4 using unmodified phosphor exhibit high steady-state light intensity, their afterglow is extremely weak, making them unsuitable for afterglow applications.

[0068] In terms of mechanical properties, Examples 1-4 use KH550 modified phosphor or MF coated phosphor to obtain better flexural strength, flexural modulus and impact strength, exhibiting high strength and high rigidity, and good long-term use stability.

[0069] In summary, for applications where afterglow is the primary function and long-term performance is required, such as luminous emergency indicator devices, luminous signage devices, or luminous lighting devices, the modified phosphor, modified talc, maleic anhydride, and foaming agent compounded with PP in the embodiments of this invention can provide a long afterglow time while possessing good bending and tensile properties, thus meeting the usage requirements of most rigid structural components.

Claims

1. A luminescent polypropylene composite material, characterized in that, The composition comprises the following components in parts by weight: 150-250 parts polypropylene, 1-12 parts modified phosphor, 8-12 parts modified talc, 8-12 parts maleic anhydride, and 2-6 parts foaming agent; wherein the modified phosphor includes aminosilane coupling agent modified phosphor, melamine-formaldehyde resin coated phosphor, or a combination thereof. The modified talc includes talc modified with an aminosilane coupling agent.

2. The luminescent polypropylene composite material according to claim 1, characterized in that, The aminosilane coupling agent is selected from γ-aminopropyltriethoxysilane.

3. The luminescent polypropylene composite material according to claim 1, characterized in that, The aminosilane coupling agent content in the modified phosphor is 1-5%; And / or, the aminosilane coupling agent content in the aminosilane coupling agent modified talc is 1~5%.

4. The luminescent polypropylene composite material according to claim 1, characterized in that, The melamine-formaldehyde resin-coated phosphor is prepared by a method comprising the following steps: mixing melamine, formaldehyde and water to obtain a melamine-formaldehyde prepolymer solution; mixing the melamine-formaldehyde prepolymer solution, phosphor and an acidic compound, and performing a polymerization reaction to obtain the melamine-formaldehyde resin-coated phosphor.

5. The luminescent polypropylene composite material according to claim 1, characterized in that, The mass of the modified phosphor is 0.05 to 6% of the mass of the polypropylene.

6. The luminescent polypropylene composite material according to claim 1, characterized in that, The mass of the modified talc is 3 to 7% of the mass of the polypropylene.

7. The luminescent polypropylene composite material according to claim 1, characterized in that, The components of the luminescent polypropylene composite material also include white oil.

8. A method for preparing a phosphorescent polypropylene composite material as described in any one of claims 1 to 7, characterized in that, Includes the following steps: The components are mixed and extruded to obtain the luminescent polypropylene composite material.

9. The preparation method according to claim 8, characterized in that, The extrusion granulation temperature is 180~220℃; And / or, the screw speed for the extrusion granulation is 20~40 r / min.

10. The application of a luminescent polypropylene composite material as described in any one of claims 1 to 7 in a luminescent device.